2010
DOI: 10.1109/tbme.2009.2039643
|View full text |Cite
|
Sign up to set email alerts
|

A Fast and Efficient Method to Compensate for Brain Shift for Tumor Resection Therapies Measured Between Preoperative and Postoperative Tomograms

Abstract: In this paper, an efficient paradigm is presented to correct for brain shift during tumor resection therapies. For this study, high resolution pre-operative (pre-op) and post-operative (post-op) magnetic resonance images were acquired for 8 in vivo patients, and surface/subsurface shift was identified by manual identification of homologous points between the pre-op and immediate postop tomograms. Cortical surface deformation data was then used to drive an inverse problem framework. The manually identified subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 31 publications
1
73
0
Order By: Relevance
“…This could be explained by the early timing of the postoperative scans (all scans were acquired within 25 h of surgery) (see Table IV). In some respects, this does lend credence to our previous investigations [8] where the correction approach was driven by cortical surface points extracted from pre- and postoperative MRI points and validated against subsurface corresponding target points.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…This could be explained by the early timing of the postoperative scans (all scans were acquired within 25 h of surgery) (see Table IV). In some respects, this does lend credence to our previous investigations [8] where the correction approach was driven by cortical surface points extracted from pre- and postoperative MRI points and validated against subsurface corresponding target points.…”
Section: Discussionsupporting
confidence: 72%
“…The pipeline of tasks in this process from the preoperative stages of mesh generation and boundary condition assignment to intraoperative data acquisition and image update has been reported in other work [4], [8], [9] and are summarized in the Appendix. While this framework is potentially powerful, the ability to characterize a resection cavity with a low-encumbrance device like the conoprobe during surgery may potentially inform this framework.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been shown that local volumetric brain deformation can be inferred given the cortical surface displacement [34]. In this context, inside the framework of the European project ACTIVE, a series of high-resolution model deformations based on brain constitutive law and complex loading conditions, such as brain shift due to gravity, organ volume changes due to drug reactions or due to edema, were developed.…”
Section: Discussionmentioning
confidence: 99%